Continuous Glucose Monitoring (CGM) in Type-1 Diabetes Mellitus: A Promising Aid in Effective Management - Kumud Dhankhar; Rakesh Dhankhar; Kiran Dahiya; Kabir Dhankhar; Rajandeep Singh; Chandini Dash; Ajay Momi (Medical Research and Its Applications Vol. 11, 2024)
Considering the large, global prevalence of diabetes mellitus, there is an increasing demand for effective and innovative management aids. Monitoring of glucose levels is an essential component of diabetes care. Continuous glucose monitoring (CGM) is becoming widely accepted as an adjunct to diabetes management. It can provide real-time data on ambulatory glucose fluctuations and carries the potential to become a very valuable tool for a large part of the population worldwide. This chapter entails a thorough literature review of the evolution of CGM devices, its working principles, recent breakthroughs, patient selection, areas with scope for more research, merits as well as drawbacks of CGM in patients of Type-1 diabetes mellitus.